Pengaruh Pemberian Remunerasi Direksi Terhadap Kinerja Keuangan Perusahaan Publik di Indonesia - Amadea Paulina Pangestu; Selly Agustia; Rathria Arrina Rachman (Universitas Prasetiya Mulya, 2019)
This research was conducted to study the relationship between remuneration of directors and financial performance of companies in Indonesia. Based on the Agency Theory (Jensen and Meckling, 1976), remuneration given to directors will improve the company's financial performance because the provision of good remuneration will harmonize the interests of the principal (shareholders) and agents (company directors). This study uses a sample of 147 publicly-listed companies spread across 10 sectors and listed on the Indonesia Stock Exchange over 2013 to 2017. Using panel data regression methods with Generalized Least Squares (GLS),, the results of this study indicate that the remuneration of directors has a positive relationship to several financial performance indicators, namely Return On Assets (ROA) and Return On Equity (ROE, where the higher the remuneration given to directors will improve the company's financial performance. Thus, this results is consistent with the Agency Theory.